PERLINDUNGAN HAK ASASI MANUSIA BAGI KARYAWAN PERUSAHAAN MILITER DAN KEAMANAN SWASTA: ANALISIS HUKUM NORMATIF DALAM PERSPEKTIF HUKUM INTERNASIONAL DAN NASIONAL - Mulawarman, Devantara Pranata; Kurnia, Mahendra Putra; Erawaty, Rika (Jurnal Ilmiah Advokasi, 2025)
This study examines the legal basis for Human Rights Protection of Private Military and Security Company (PMSC) employees. Despite frequent violations of their rights, no binding international law currently regulates this matter. The purpose is to identify the existing legal framework and potential measures to enhance protection. This research applies a normative juridical (doctrinal) method by analyzing international humanitarian law, human rights instruments, and comparative approaches. The findings reveal that the absence of binding law leads to legal uncertainty and vulnerability for PMSC employees, with several documented cases of human rights violations. The study concludes that strengthening international instruments and harmonizing national laws are crucial to ensure effective human rights protection for PMSC employees. Keywords: Human Rights; Humanitarian Law; Private Military and Security Company; Workers’ Rights